Program Open Laboratory Fisika untuk Mendukung Pembelajaran Praktikum di Sekolah Menengah - Nurul Ain; Hestiningtyas Yuli Pratiwi; Muhammad Sayyadi; Akhmad Jufriadi (Jurnal Pengabdian Masyarakat, 2025)
The limited physics laboratory facilities and infrastructure in high schools remains a major obstacle to meaningful physics learning. Trimurti High School is one of the schools that does not yet have a physics laboratory, so the learning process tends to be conducted through lectures and minimal practical activities. This community service activity aims to provide a practical-based learning experience through an open physics laboratory program involving lecturers and students. The practicals implemented include the formation of images on convex and concave lenses, the use of a simple microscope, and experiments with straight-line motion. The community service method is carried out through the stages of planning, implementation of the practical, and evaluation of the activity. The results of the activity showed a very enthusiastic response from teachers and students, increased learning motivation, and a better understanding of physics concepts through direct experience. This open laboratory activity is expected to be an alternative solution for schools with limited laboratory facilities and encourage the implementation of more contextual and active physics learning.